(untitled) (Revista de História da UEG (REVHIST), 2021)
The present paper seeks to explore the concept of Political Culture, observing its initial definitions and the development of studies derived from this approach. Its characteristics, scope and methodology are analyzed through a theoretical foundation and, later, with the illustration of studies of political culture in history. The purpose of this activity is to outline the definition of this concept more clearly and its contribution to analytical thinking. Keywords: Culture. Political. Historiography. Methodology. Theory.